1998
DOI: 10.1148/radiology.208.2.9680558
|View full text |Cite
|
Sign up to set email alerts
|

Breath-hold gadolinium-enhanced MR angiography of the major vessels at 1.0 T: dose-response findings and angiographic correlation.

Abstract: The clinical gadolinium dose of 0.1 mmol/kg is sufficient for diagnostic assessment of the aorta and its major branches at contrast-enhanced MR angiography. High-dose studies appear not to be required for these large vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 0 publications
2
18
0
5
Order By: Relevance
“…This study shows that to achieve appropriate arterial enhancement, the concentration of gadolinium chelate is less important than the overall dose, as previously reported [16,18]. The differences observed in the present study did not relate directly to the length of renal arteries opacified, but to the amount of vascular enhancement.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This study shows that to achieve appropriate arterial enhancement, the concentration of gadolinium chelate is less important than the overall dose, as previously reported [16,18]. The differences observed in the present study did not relate directly to the length of renal arteries opacified, but to the amount of vascular enhancement.…”
Section: Discussionsupporting
confidence: 71%
“…This technique, bolus tracking [15], involves using a test bolus to find the optimum interval between contrast injection and imaging. A major disadvantage of the technique is the necessity of waiting for the contrast to diminish (about 5 min) after the test bolus [16]. In our study, we did not use the test bolus examination because this would have caused accumulation of contrast medium in the renal pelvis and increased overall vessel enhancement, including venous enhancement, neither of which is generally desirable [10].…”
Section: Discussionmentioning
confidence: 95%
“…Factors that might explain the present results could be the predetermined choice of a fairly low dose of 0.1 mmol/kg, the inclusion criteria for MR imaging, the prolonged duration of our multicenter study, and the image evaluation with a reading of DSA images in consensus versus that with an independent blinded reading of MR angiographic images. (24) refer to a decrease in the signal-tonoise ratio with reduction of the repetition and echo times that would require a higher dose. Thus, in our study, with a mean repetition time of 4.35 msec Ϯ 0.80 and a mean echo time of 1.41 msec Ϯ 0.24 at 1.5-T imaging and with a mean repetition time of 6.28 msec Ϯ 0.82 and a mean echo time of 1.92 msec Ϯ 0.38 at 1.0-T imaging, a higher dose should have been used, and a dose of at least 0.15-0.20 mmol/kg should have been used for sufficient evaluation of the smaller branches of the aorta or the pelvic arteries, such as the inferior mesenteric artery or the internal iliac arteries (25).…”
Section: Discussionmentioning
confidence: 99%
“…Second, first-pass of contrast medium mainly contributed to imaging of carotid artery 15,[18][19][20] , so that the residual of contrast medium didn't play an important role for the first-pass of contrast medium bolus. In one study of aorta and its major branches using same contrast-enhanced MRA sequence, the authors observed that neither vessel en- hancement nor diagnostic information was significantly different across the three study groups with different dosage of contrast medium 21 . In the head and neck region, jugular venous contamination is a problem for contrastenhanced MR angiography because blood-brain barrier prevents extraction of the gadolinium chelate in the intracerebral circulation and the interval from carotid arterial enhancement to jugular venous enhancement is short.…”
Section: Discussionmentioning
confidence: 99%